Boosting the stable sodium-ion storage performance by tailoring the 1D TiO2@ReS2 core-shell heterostructures. (1st April 2020) - Wang, Xinqian; Chen, Biao; Mao, Jing; Sha, Junwei; Ma, Liying; Zhao, Naiqin; He, Fang
Abstract: ReS2 has been considered as an emerging transition metal dichalcogenides (TMDs) material for sodium-ion batteries (SIBs). However, its electrochemical performance is severely limited by the structural aggregation and damage during deep charge-discharge. Here, a new 1D TiO2 @ReS2 core-shell structure is reported for boosting the stable performance as the TiO2 has durable structural stability. The 1D TiO2 nanotubes with rough surface and large surface area are helpful to grow few-layer (≤4 layers) ReS2 nanosheets onto their surface. In the obtained 1D TiO2 nanotube@ReS2 nanosheet (1D TiO2 -NT@ReS2 -NS) core-shell heterostructures, the exposed ultrathin ReS2 nanosheets offer high contact area for rapid Na + diffusion, whilst the TiO2 nanotubes work as robust backbone for accommodating volume change and strain. Moreover, the chemical interfacial interaction between TiO2 and ReS2 gives rise to favorable synergistic effect, leading to enhanced electrical conductivity, Na + diffusion kinetics, and structural stability at both electrode and materials levels. These findings can be supported by various characterization technologies such as X-ray photoelectron spectrum and high-resolution transmission electron microscopy. As a result, the 1D TiO2 -NT@ReS2 -NS electrode displays a desirable long-life span cycling performance of 118 mAh g −1 at 1 A g −1 after 1000 cycles in sodium-ion batteries. This work not only reports a stable SIBs anode material, but also provides fundamental understanding for designing and fabricating electrode materials for alkali metal ion batteries. Highlights: Rational design of 1D TiO2 -NT@ReS2 -NS core-shell structure through a facile hydrothermal method. 1D TiO2 -NT@ReS2 -NS exhibited excellent long-life span cycling performance in SIBs. 1D TiO2 -NT@ReS2 -NS provide fast electrical transport path and facilitate the Na + diffusion kinetics. The strong interfacial interaction effectively accommodate volume change and strain of ReS2 .